The influence of support program in the development of thermal irrigation canal on rice production improvement in Pohuwato District - Amir Halid; Muh. Amir Archam; Sri Astuti Manoppo (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
The purposes of this research are: 1) to analyze the implementation system of tertiary irrigation assistance in Pohuwato District, 2) To study the tertiary irrigation development assistance program that affect the increase of rice production in Pohuwato. The study was conducted in Pohuwato District with 93 farmers sample. The research method used is survey method. Data analysis used is descriptive analysis with percentage formula and multiple linear regression analysis. The results showed that the system of tertiary irrigation implementation from the assessment of the percentage of total score of respondents answers on the program policy indicators included in the category is quite good, and on the indicator of increased production percentage total score of respondents' answers included in the category very well. So that the application of tertiary irrigation aid in the research location has been well developed in the aid of tertiary irrigation canal program.The results that the program of development assistance of tertiary irrigation canals on rice farming simultaneously have a positive and significant effect on increasing rice production. While partially independent variable (program policy, farmer institute, and tertiary irrigation canal) to dependent variable of rice production.